2013
DOI: 10.1088/0031-9155/58/22/8215
|View full text |Cite
|
Sign up to set email alerts
|

Proton radiography and proton computed tomography based on time-resolved dose measurements

Abstract: We present a proof of principle study of proton radiography and proton computed tomography (pCT) based on time-resolved dose measurements. We used a prototype, two-dimensional, diode-array detector capable of fast dose rate measurements, to acquire proton radiographic images expressed directly in water equivalent path length (WEPL). The technique is based on the time dependence of the dose distribution delivered by a proton beam traversing a range modulator wheel in passive scattering proton therapy systems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…Thus, images acquired by proton integrating system suffered from edge artifacts at the interfaces between materials, 15 overall low spatial resolution, and relatively large SPR error. 22 In 2018, Zhang et al developed a proton integrating radiography system that measured the so-called time-resolved dose rate functions (DRFs), and derived water equivalent path length based on intensity weighted root-mean-square of DRFs. 23 The error of SPR was claimed to be within AE 1%, and the detector pixel pitch was 0.388 mm, which was promising for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, images acquired by proton integrating system suffered from edge artifacts at the interfaces between materials, 15 overall low spatial resolution, and relatively large SPR error. 22 In 2018, Zhang et al developed a proton integrating radiography system that measured the so-called time-resolved dose rate functions (DRFs), and derived water equivalent path length based on intensity weighted root-mean-square of DRFs. 23 The error of SPR was claimed to be within AE 1%, and the detector pixel pitch was 0.388 mm, which was promising for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these works focus on the usage of carbon ions due to the less pronounced MCS, which is especially important for nontracking systems. The reported applied doses for these systems are rather high, for example, 7 mGy for one radiograph or 8 Gy for one CT …”
Section: Introductionmentioning
confidence: 99%
“…Integrating systems measure the integrated signal of the particles downstream of the object being imaged (pRad: 14,15 ; iRad: 16 ; pCT: 17 ; iCT: 16,[18][19][20]. Most of these works focus on the usage of carbon ions due to the less pronounced MCS, which is especially important for nontracking systems.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that the patientspecific calibration curves (converting the x-ray CT dataset to units of RSP) can be generated through an optimization procedure together with the original x-ray CT. 8 In addition to reducing the proton beam range uncertainty in proton treatment planning, proton radiography has a number of other potential applications, including convenient patient setup, 9 passive range verification, 8 and active range verification. 10 One of the major disadvantages of proton radiography is due to the fact that protons undergo multiple Coulomb scattering (MCS) in the patient, which limits the spatial resolution compared to x-ray imaging. 11 This physical process has driven the classical approach to proton radiography in which attempts are made to correct for MCS by tracking protons before and after the patient and by measuring the residual proton energy at the patient exit.…”
Section: Introductionmentioning
confidence: 99%
“…3,17,35 The measurement of dose offers a simple approach to proton radiography. A range of such techniques have been tested, including using pairs of sloped spread-out Bragg peaks (SOBPs), 36,37 measuring the time-resolved dose from a proton beam passively scattered by a range modulator wheel, 10,38,39 and by measuring the ratio of doses of two pristine Bragg peaks, 40 which is the subject of this work. The technique works as follows: (1) measure depth dose curves in water for two pristine Bragg peaks; (2) determine the "dose ratio curve" for the energy pair by dividing the lower energy by the higher energy; (3) record the dose map beyond an object of unknown thickness/material for each of the two energies and calculate the dose ratio map; and (4) convert to a WET using the dose ratio curve.…”
Section: Introductionmentioning
confidence: 99%